Personal Selling, Brand Image Dan Brand Trust Universitas Dalam Keputusan Studi Mahasiswa - Fariz Hilman Perdana; Yuli Kartika Dewi; Cosmas Gatot Haryono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Study decisions at private universities are becoming increasingly complex because prospective students face many institutional choices, uncertainty regarding the quality of educational services, and long-term investment risks. This study aims to analyze the influence of personal selling and brand image on study decisions through brand trust. Data were obtained through a survey of 119 second-semester active students at a private university in Banyuwangi, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that brand image builds brand trust and drives study decisions, while brand trust mediates the relationship between brand image and study decisions. Personal selling builds brand trust but is not sufficient to drive study decisions, either directly or through brand trust. These findings indicate that study decisions are more strongly explained by trust built through institutional image than by direct interpersonal communication. This study extends the application of the Stimulus–Organism–Response (SOR) framework in higher education marketing by demonstrating that institutional image is a more effective stimulus to be converted into decisions through trust. This implies that private universities need to maintain consistency of image, information credibility, and evidence of institutional quality in their student recruitment strategies.